DNA pairing is an important step in the process of targeted nucleotide exchange - Drury, Miya D. (Oxford University Press, 2003)
Modified single-stranded DNA oligonucleotides can direct the repair of genetic mutations in yeast, plant and mammalian cells. The mechanism by which these molecules exert their effect is being elucidated, but the first phase is likely to involve the homologous alignment of the single strand with its complementary sequence in the target gene. In this study, we establish the importance of such DNA pairing in facilitating the gene repair event. Oligonucleotide-directed repair occurs at a low frequency in an Escherichia coli strain (DH10B) lacking the RECA DNA pairing function. Repair activity can be rescued by using purified RecA protein to catalyze the assimilation of oligonucleotide vectors into a plasmid containing a mutant kanamycin resistance gene in vitro. Electroporation of the preformed complex into DH10B cells results in high levels of gene repair activity, evidenced by the appearance of kanamycin-resistant colonies. Gene repair is dependent on the formation of a double-displacement loop (double-D-loop), a recombination intermediate containing two single-stranded oligonucleotides hybridized to opposite strands of the plasmid at the site of the point mutation. The heightened level of stability of the double-D-loop enables it to serve as an active template for the DNA repair events. The data establish DNA pairing and the formation of the double-D-loop as important first steps in the process of gene repair.